Philosophical Approach to Education in the Concept of an Independent Curriculum - Nida Amalia Manggala; Sofyan Sauri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The concept of education cannot be separated from philosophical thinking. Basically, the meaning related to the concept of education discusses human nature. Therefore, the development of education in Indonesia must be based on philosophical approaches. Currently, curriculum development in Indonesia is a hot topic of conversation. The Minister of Education and Culture launched the Independent Curriculum which is a solution to the learning loss problem that occurred during the Covid-19 pandemic. The Merdeka curriculum is here to be a breath of fresh air in the world of education. This research aims to determine the philosophical approach to the Independent Curriculum. The research method used is Systematic Literature Review (SLR). The research results show that the concept of a curriculum, especially the Independent Curriculum, cannot be separated from the philosophical approach to education. The philosophical approach in the Independent Curriculum is viewed from three approaches, namely the speculative approach, the value approach, and the radical critical approach. The speculative approach sees the formation of the Independent Curriculum based on the overall view, especially in the current good educational situation. The normative approach contains the values to be raised in the curriculum concept where the Merdeka Curriculum emphasizes the values of the Pancasila Student Profile. The radical crisis approach looks at how the Independent Curriculum is implemented in schools. It can be concluded that in forming a curriculum, consideration of educational philosophical views is needed.